Gigoo, Arvind, The Ugly Kashmiri (Cameos in exile), (2ª ed.), Nueva Delhi, Allied Publishers, 2008, 108 pp. - Hari Nair (El Colegio de México, A.C., 2009)
Gigoo, Arvind, The Ugly Kashmiri (Cameos in exile), (2ª ed.), Nueva Delhi, Allied Publishers, 2008, 108 pp.